Energy efficiency based on capacitor sizing and placement using monte carlo technique / Siti Nur A'rfah Shamsudin - Shamsudin, Siti Nur A'rfah (2014)
The reactive power compensation plays the important role in the planning of power system. These ensure a reduction in power and energy losses within the system. Reactive power that is injected by using the capacitor can also can improve the power factor in the system. The benefit to improve the power factor is reduced maximum demand, improved the voltage profile, minimizing the cost of compensation and improved power quality. This thesis is concerned about the reactive compensation of power system that is attempt using the capacitor. The capacitor placement and sizing is determined using the Monte Carlo technique. Monte Carlo technique allows the sizing and placement of capacitor optimally selected based on minimization of power loss. The reactive power compensation of power system is analyzed by using the simulation model of the distribution system in the Matlab software.